Situation Report: Romania, 16 August 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Recent Changes of County Party First Secretaries Insufficient Utilization of Industrial Production Capacity Romania's Participation in the World Youth Festival New Commander of the Navy? Ideological Contacts Second Consecutive Bumper Wheat Crop? Literary Controversy Continues Law on Illicitly Acquired Property Amended